Implications of movement behavior responses of both Asian and African elephants in changing landscapes of the 21st century - Chan, Aung Nyein, author; Wittemyer, George, advisor; Leimgruber, Peter, committee member; Noon, Barry, committee member; Aldridge, Cameron, committee member (Colorado State University. Libraries, 2023)
An organism moves to fulfil its most fundamental survival and reproductive needs. Studying movement behavior can provide insights into both inter- and intra-specific interactions, how a species interacts with its environment and accesses resources, species distribution, etc. Given human presence affects mammalian movement across the globe, animal movement studies are increasingly important to assess and understand the impacts of humans on wildlife. Movement behavior response to human presence is particularly relevant and important to understand in the 21st century since global human population is projected to reach 9.7 billion by the year 2050. The unprecedented level of human presence and associated land use changes will impact all living organisms on the planet, particularly megaherbivores such as Asian and African elephants which have some of the largest space use requirements among terrestrial mammals. My dissertation research focuses on studying and understanding the movement behavior responses of Asian and African elephants to human-related landscape changes. The Asian elephant (Elephas maximus) which is currently listed as endangered under the IUCN red list of threatened species. The population status of the species is unclear but declining. The species is facing habitat loss and fragmentation due to agricultural expansion, heightened human-elephant conflicts related to human encroachment in previous wilderness areas, and illegal killings, including but not limited to, poaching for skin, ivory, and meat. The largest remaining tracts of wildland (i.e., habitat suitable for wild elephant to exist) among the current extant range countries/states occurs in the country of Myanmar. However, the struggling economy and unstable political climate put unusual amount of stress on the remaining elephant populations across the country. Asian elephant numbers are declining across much of their range in Myanmar, driven largely by serious threats from land use change resulting in habitat loss and fragmentation. To effectively manage and conserve the remaining populations of endangered elephants in the country, it is crucial to understand their movement behavior across the country's agricultural gradient. Chapter 1 provided baseline information on elephant spatial requirements and the factors affecting them in Myanmar. This information is important for advancing future land-use planning that considers space-use requirements for elephants. Failing to do so may further endanger already declining elephant populations in Myanmar and across the species' range. We used autocorrelated kernel density estimator (AKDE) based on a continuous-time movement modeling (ctmm) framework to estimate dry season (26 ranges from 22 different individuals), wet season (12 ranges from 10 different individuals), and annual range sizes (8 individuals), and reported the 95%, 50% AKDE, and 95% Minimum Convex Polygon (MCP) range sizes. We assessed how landscape characteristics influenced range size based on a broad array of 48 landscape metrics characterizing aspects of vegetation, water, and human features and their juxtaposition in the study areas. To identify the most relevant landscape metrics and simplify our candidate set of informative metrics, we relied on exploratory factor analysis and Spearman's rank correlation coefficients. Based on this analysis we adopted a final set of metrics into our regression analysis. In a multiple regression framework, we developed candidate models to explain the variation in AKDE dry season range sizes based on the previously identified, salient metrics of landscape composition. Our objectives were to (1) estimate the sizes of dry, wet, and annual ranges of wild elephants in Myanmar; and quantify the relationship between dry season (the period when human-elephant interactions are the most likely to occur) range size and configurations of agriculture and natural vegetation within the range, and (2) evaluate how percentage of agriculture within dry core range (50% AKDE range) of elephants relates to their daily distance traveled. Elephant dry season ranges were highly variable, averaging 792.0 km2 and 184.2 km2 for the 95% and 50% AKDE home ranges, respectively. We found both the shape and spatial configuration of agriculture and natural vegetation patches within an individual elephant's range play a significant role in determining the size of its range. We also found that elephants are moving more (larger energy expenditure) in ranges with higher percentages of agricultural area. Chapter 2 reveals how elephants interact with agriculture and other important environmental variables such as natural vegetation, roads, and water, etc. Habitat loss and fragmentation due to accelerated agriculture expansion is a major threat to existing wildlife populations across Asia. Although it had been shown that Asian elephant space use was correlated with the level of fragmentation on the landscape in Chapter 1, the mechanism underlying this process is not well documented and can serve to help focus conservation efforts. We analyzed selection behavior of wild elephants across three study sites with different levels of agriculture use patterns in Myanmar, assessing the impact of structure in the agriculture- wildlands interface on habitat selection by elephants. Given elephants exhibit heterogeneous spatial behavior, we fitted two types of selection models to gain insight into the diversity of strategies employed at the local- and home-range scale. We used variance partitioning analysis to quantify the explanatory contribution of individual, study site, and sex. We found that the variation in the resource selection behavior was mainly due to individual differences, and the level of agriculture present in an individual's range was the most influential to its selection behavior. Gaining a deeper understanding of habitat selection behavior by elephants across the changing landscapes of Asia can help inform management decisions and conservation actions. As the military coup in 2021 in Myanmar affected my ability to continue working in Myanmar, we decided to transition into assessing the connectivity between Etosha National Park and an adjacent Kunene multi-use conservancies area in Namibia for African elephant (Loxodonta africana) as Chapter 3. This region is of particular importance in African elephant conservation since the population is doing relatively well in the area and could serve as one of the remaining strongholds for the species. The loss of habitat and fragmentation of landscapes could lead to declines in wildlife populations, highlighting the need to identify and preserve critical habitats. Connectivity between populations plays a crucial role in mitigating the risks faced by small populations and ensuring their long-term persistence. As a result, the identification of corridors has become a key objective in wildlife conservation. Various methods have been developed to identify high connectivity locations, including resistance surface modeling and empirical-based approaches using GPS tracking data. We used GPS telemetry data from 66 elephants to empirically quantify connectivity using a graph-theoretic approach and assessed landscape features influencing connectivity. We applied the 'movescape' approach to define and locate different types of corridors and examined how landscape features differed across these corridors. Our results revealed strong variation in connectivity across the landscape, with paths of high connectivity near water sources between the study areas. We found that factors related to water sources and human presence primarily influenced connectivity. The findings of this study provide valuable insights into the connectivity patterns and landscape features influencing connectivity for African elephants in northwestern Namibia. We discussed this findings in the context of future conservation management scenarios. Finally, Chapter 4 assessed the current knowledge on population status of Asian elephants across all 13 range countries or states. We conducted a literature search on Google Scholar using keywords, "Asian elephants", "Population size", "Abundance", and "Density". We found 26 articles and 9 governmental and non-governmental reports from 2000 to 2022 to evaluate the extent of population assessments using statistically robust methods. Our findings indicate that only 4.39% of the current known distribution of Asian elephants had been assessed using robust sampling and statistical approaches. Out of the 13 range states, only 7 had conducted assessments, with only 3 countries performing robust population assessments in the last 5 years. We highlight the urgent need for more comprehensive and up-to-date studies to accurately estimate the population size of Asian elephants. We recommend investing in spatial capture- recapture approaches using fecal-DNA and photographic capture-recapture methods where feasible to improve abundance estimation. The results of this review emphasize the critical role of accurate population knowledge for effective conservation and management actions for endangered species like the Asian elephant. This dissertation provides critical pieces of information regarding movement ecology and conservation of both Asian elephant and African elephant. We present analyses on space use requirements, resource selection behavior and the quantification of sources of variation in the movement behavior for Asian elephant in Myanmar. Chapter 1 and chapter 2 were the first two studies to assess movement behavior in Myanmar using empirical data. Since identifying and conserving corridors is one of the key objectives for African elephant's conservation, chapter 3 provides crucial information for managers on the ground in Etosha National Park and surrounding areas. Finally, we highlighted the research gap in Asian elephant conservation by reviewing studies and reports on population status across the species' range.
Keywords: Asian elephant; Myanmar; African elephant; Namibia; movement ecology